IMPACT OF CHANGING DEMOGRAPHICS ON SERVICE DELIVERY OF COMPANIES. A CASE OF MTN UGANDA CUSTOMER SERVICE CENTERS IN KAMPALA UGANDA. - Kambale Kamate Jacob (2024, 2024)
The study focused on examining the impact of changing demographics on service delivery in MTN Customer service centers in Kampala Uganda. the study was guided by the following objectives: to examine the impact of age on service delivery of companies; to assess the impact of sex on service delivery of companies.; and, to assess the impact of marital and family status on service delivery of companies. In order to give a thorough analysis of the research problem and explore the nature of the relationship between study variables while concentrating on the case's dynamics within its actual setting, a case study research design was used in this study. Furthermore, the majority of the study's methodologies were quantitative. The study used 40 respondents from MTN Centers in Kampala as a sample size. Data was collected using a questionnaire. Data was analyzed through use of percentages, means and standard deviations. Data was presented using frequency tables and interpreted using standard deviations. The study concluded that age has a significant impact on service delivery as it determines easy access to service, affects the way customer care is provided and also determines quality of service. Staff behaviour and attitudes are also decided by the age of staff. The study also concluded that confidentiality is also determined by age. The study also concluded that does not impact service delivery as it does not increase one’s capacity to offer periodic follow-up to services delivered, does not enhance improved public information to customers, improved information sharing with customers is not determined by a staff’s gender and gender of a staff also does not determine how a staff attends customer complaints on time. The study further concluded that the impact of marital and family status on service delivery is substantial as marital and family status determines quality of service, whereas staff behavior and attitudes are also decided by the marital and family status of staff. The study recommends that age should be considered in matters of service delivery as it determines easy access to service, affects the way customer care is provided and also determines quality of service. More so, staff behaviour and attitudes that are also decided by the age should put into consideration when recruiting staff. The study also concluded that confidentiality should also be determined by age as older people tend to keep secrets of customers especially sensitive customer personal details. The study also recommends that gender should be concentrated on when determining service delivery parameters as it does not increase one’s capacity to offer periodic follow-up to services delivered and it does not enhance improved public information to customers or information sharing with customers. The study also recommends that the impact of marital and family status on service delivery should be emphasized it determines quality of service, whereas staff behavior and attitudes are also decided by the marital and family status of staff.